Interferon-Independent Innate Responses to Cytomegalovirus - Ashley, Caroline L.; Abendroth, Allison; McSharry, Brian P.; Slobedman, Barry (Frontiers in Immunology, 2019)
The critical role of interferons (IFNs) in mediating the innate immune response to cytomegalovirus (CMV) infection is well established. However, in recent years the functional importance of the IFN-independent antiviral response has become clearer. IFN-independent, IFN regulatory factor 3 (IRF3)-dependent interferon-stimulated gene (ISG) regulation in the context of CMV infection was first documented twenty years ago. Since then several IFN-independent, IRF3-dependent ISGs have been characterized and found to be among the most influential in the innate response to CMV. These include virus inhibitory protein, endoplasmic reticulum-associated IFN-inducible (viperin), ISG15, members of the interferon inducible protein with tetratricopeptide repeats (IFIT) family, interferon-inducible transmembrane (IFITM) proteins and myxovirus resistance proteins A and B (MxA, MxB). IRF3-independent, IFN-independent activation of canonically IFN-dependent signaling pathways has also been documented, such as IFN-independent biphasic activation of signal transducer and activator of transcription 1 (STAT1) during infection of monocytes, differential roles of mitochondrial and peroxisomal mitochondrial antiviral-signaling protein (MAVS), and the ability of human CMV (HCMV) immediate early protein 1 (IE1) protein to reroute IL-6 signaling and activation of STAT1 and its associated ISGs. This review examines the role of identified IFN-independent ISGs in the antiviral response to CMV and describes pathways of IFN-independent innate immune response induction by CMV.